Phase II study of first‐line trebananib plus sorafenib in patients with advanced hepatocellular carcinoma - Abou-Alfa, Ghassan K.; Ganten, Tom M. (The oncologist, 2017)
Lessons Learned. Trebananib leveraging anti‐angiogenic mechanism that is distinct from the classic sorafenib anti‐vascular endothelial growth factor inhibition did not demonstrate improved progression‐free survival at 4 months in patients with advanced hepatocellular carcinoma (HCC). In support of previously reported high Ang‐2 levels’ association with poor outcome in HCC for patients, trebananib treatment with lower baseline Ang‐2 at study entry was associated with improved overall survival to 22 months and may suggest future studies to be performed within the context of low baseline Ang‐2. Background. Ang‐1 and Ang‐2 are angiopoietins thought to promote neovascularization via activation of the Tie‐2 angiopoietin receptor. Trebananib sequesters Ang‐1 and Ang‐2, preventing interaction with the Tie‐2 receptor. Trebananib plus sorafenib combination has acceptable toxicity. Elevated Ang‐2 levels are associated with poor prognosis in hepatocellular carcinoma (HCC). Methods. Patients with HCC, Eastern Cooperative Oncology Group ≤2, and Childs‐Pugh A received IV trebananib at 10 mg/kg or 15 mg/kg weekly plus sorafenib 400 mg orally twice daily. The study was planned for ≥78% progression‐free survival (PFS) rate at 4 months relative to 62% for sorafenib historical control (power = 80% α = 0.20). Secondary endpoints included safety, tolerability, overall survival (OS), and multiple biomarkers, including serum Ang‐2. Results. Thirty patients were enrolled sequentially in each of the two nonrandomized cohorts. Demographics were comparable between the two arms and the historical controls. PFS rates at 4 months were 57% and 54% on the 10 mg/kg and 15 mg/kg trebananib cohorts, respectively. Median OS was 17 and 11 months, respectively. Grade 3 and above events noted in ≥10% of patients included fatigue, hypertension, diarrhea, liver failure, palmar‐plantar erythrodysesthesia syndrome, dyspnea, and hypophosphatemia. One death was due to hepatic failure. Serum Ang‐2 dichotomized at the median was associated with improved OS in both cohorts. Conclusion. There was no improvement in PFS rate at 4 months in either cohort, when compared with sorafenib historical control.